Isotopic composition of oxygen in igneous rocks of Pohorje - Dolenec, Tadej; Pezdič, Jože; Strmole, Dragica (Geologija, 1987)
First data on the isotopic composition of oxygen and carbon in tonalite and cezlakite from the pegmatitic and aplitic veins of Mt. Pohorje were obtained by mass spectrometric analysis. It has been established that tonalite which is more felsic than cezlakite contains higher amounts of the heavy oxygen isotope. According to first data the mother magma of this Pohorje intrusive rock with δ18O +9.1 ‰ was of juvenile origin, admitting the possibility of partly assimilation of rocks of the Continental crust which were enriched withe the heavy isotope. The enrichment of the cezlakite with the light oxygen isotope seems to be the consequence of its composition. The rock is basic with the δ18O value +7.1 ‰. It contains more than fifty percent of augite and hornblende, i. e. minerale with a lower ability of concentration of heavy oxygen isotope with respect to quartz. The latter is next to feldspars the most abundant mineral in tonalite. The isotopic composition of oxygen of cezlakite is in the area which is typical for gabbroid rocks. The aplitic and pegmatitic veins in tonalite and aplitic veins in cezlakite contain mostly more heavy oxigen isotope than the mentioned igneous rocks. Among all minerals in the pegmatitic veins quartz has the highest value of δ18O.